2017
DOI: 10.2217/fmb-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

USP19 Suppresses Cellular type I Interferon Signaling by Targeting TRAF3 for Deubiquitination

Abstract: This work suggests that USP19 is a previously unrecognized regulator employed by EV71 to evade host antiviral defenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Therefore, we speculate that USP4 plays an essential role in antiviral immune response. USP4 has previously been confirmed to target TRAF2 and TRAF6 for deubiquitination and it has been established that USP4 inhibits TNFα-induced cancer cell migration 35 . It was confirmed that USP4 associates with TRAF2 and TRAF6, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculate that USP4 plays an essential role in antiviral immune response. USP4 has previously been confirmed to target TRAF2 and TRAF6 for deubiquitination and it has been established that USP4 inhibits TNFα-induced cancer cell migration 35 . It was confirmed that USP4 associates with TRAF2 and TRAF6, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The USPs are the biggest subfamily with more than 50 members 33 , with some of them known to regulate antiviral immune responses 28 , 34 , 35 . Previous studies have indicated that EV71 infection induces the up-regulation of USP19, which negatively regulates the antiviral type I interferon signalling by removing K-63 polyubiquitin chains from TRAF3 35 . In this study, 88 DUBs were screened in EV71-infected RD cells, and the expression of USP4 was found to be remarkably decreased at 8 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helicase RIG-I belongs to the retinoic acidinducible gene I-like receptor (RLR) family, which recognizes single/double-stranded RNA and can be activated upon N-terminal 63K polyubiquitination [66]. As a key regulator of this step, cellular DUB USP14 has been shown to directly deubiquitinylate RIG-I, which has the effect of enhancing the replication of vesicular stomatitis virus (VSV) [67]. Similarly, DUB USP19 promotes replication of enterovirus type 71 (EV71) by removing the K63 polyubiquitin chains from TRAF3 (thereby suppressing cellular type I IFN-γ signaling) [68] and deubiquitinating Beclin-1, which leads to the activation of autophagy and subsequent inhibition of TBK1/IRF3 activation and the immune response [69].…”
Section: Ubiqitination and Its Interplay With Acetylation In Neutralimentioning
confidence: 99%
“…Meanwhile, many cellular DUBs negatively regulate type I IFN signaling pathways. For example, USP3, USP38, and USP19 target RIG-I, TBK1, and TRAF3 for deubiquitination, respectively, thereby blocking the activation of type I IFN signaling pathways (Cui et al, 2014;Gu et al, 2017;Lin et al, 2016). DUB activity also has been demonstrated in many bacteria and viruses, such as Salmonella enterica serovar Typhimurium, FMDV, PRRSV, herpesviruses, coronaviruses, and bunyaviruses, and DUB Fig.…”
mentioning
confidence: 99%